A benzimidazole scaffold as a promising inhibitor against SARS-CoV-2. Issue 5 (24th March 2023) - Mudi, Prafullya Kumar; Mahanty, Ayan Kumar; Kotakonda, Muddukrishnaiah; Prasad, Sunnapu; Bhattacharyya, Subires; Biswas, Bhaskar
Abstract: The manuscript reports the green-chemical synthesis of a new diindole-substituted benzimidazole compound, B1 through a straightforward route in coupling between indolyl-3-carboxaldehyde and o-phenylenediamine in water medium under the aerobic condition at 75 ºC. The single crystal X-ray structural analysis of B1 suggests that the disubstituted benzimidazole compound crystallizes in a monoclinic system and the indole groups exist in a perpendicular fashion with respect to benzimidazole moiety. The SARS-CoV-2 screening activity has been studied against 1 × 10e4 VeroE6 cells in a dose-dependent manner following Hoechst 33342 and nucleocapsid staining activity with respect to remdesivir. The compound exhibits 92.4% cell viability for 30 h and 35.1% inhibition against VeroE6 cells at non-cytotoxic concentration. Molecular docking studies predict high binding propensities of B1 with the main protease (M pro ) and non-structural (nsp2 and nsp7-nsp8) proteins of SARS-CoV-2 through a number of non-covalent interactions. Molecular dynamics (MD) simulation analysis for 100 ns confirms the formation of stable conformations of B1-docked proteins with significant changes of binding energy, attributing the potential inhibition properties of the synthetic benzimidazole scaffold against SARS-CoV-2. Communicated by Ramaswamy H. Sarma